IMPLEMENTASI CULTURALLY RESPONSIVE TEACHING PADA MATA PELAJARAN MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Wika Hamidan Pramulya; Dwi Anggraeni Siwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of Culturally Responsive Teaching (CRT) in fifth-grade elementary school mathematics instruction and to identify the challenges encountered during the process. The study employed a qualitative approach using a case study design at SD Negeri Mertan 01, Sukoharjo Regency. Data were collected through observation, semi-structured interviews, and documentation, and were subsequently analyzed using the Miles and Huberman model. The results indicate that the implementation of Culturally Responsive Teaching proceeded systematically through the planning, implementation, and evaluation stages by utilizing traditional houses as contextual media for teaching plane geometry. This approach was found to enhance students’ conceptual understanding, active engagement, and self-confidence. Challenges identified included low interest among some students in local culture, variations in student abilities, and limitations in the quality of visual media.